2015
DOI: 10.3390/molecules201219745
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Liquid and Solid Self-Emulsifying Drug Delivery Systems for Atorvastatin

Abstract: Abstract:The objective of this work was to design and characterize liquid and solid self-emulsifying drug delivery systems (SEDDS) for poorly soluble atorvastatin. To optimize the composition of liquid atorvastatin-SEDDS, solubility tests, pseudoternary phase diagrams, emulsification studies and other in vitro examinations (thermodynamic stability, droplet size and zeta potential analysis) were performed. Due to the disadvantages of liquid SEDDS (few choices for dosage forms, low stability and portability duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 23 publications
2
54
0
7
Order By: Relevance
“…SNEDDS upon dilution with water under gentle stirring will self-nanoemulsify into oil-in-water nanoemulsion spontaneously with about 200 nm or less in average size (Eid et al, 2014a;Kuentz, 2012;Mohsin et al, 2016). Usually, SNEDDS can readily spread in the gastrointestinal tract, which is due to the digestive motility of the intestine and the stomach that provides the agitation necessary for the self-emulsification process (Czajkowska-Kośnik et al, 2015;Mahmoud, Shukr, Bendas, 2014). The selection of SNEDDS components depends on the solubilisation capacity and physicochemical and physiological properties of the drug (Dash et al, 2015;Eid, El-Enshasy, 2014a;Kale, Patravale, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…SNEDDS upon dilution with water under gentle stirring will self-nanoemulsify into oil-in-water nanoemulsion spontaneously with about 200 nm or less in average size (Eid et al, 2014a;Kuentz, 2012;Mohsin et al, 2016). Usually, SNEDDS can readily spread in the gastrointestinal tract, which is due to the digestive motility of the intestine and the stomach that provides the agitation necessary for the self-emulsification process (Czajkowska-Kośnik et al, 2015;Mahmoud, Shukr, Bendas, 2014). The selection of SNEDDS components depends on the solubilisation capacity and physicochemical and physiological properties of the drug (Dash et al, 2015;Eid, El-Enshasy, 2014a;Kale, Patravale, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The formulation with a high turbidity (2.4766 ± 0.1266 NTU) had Smix ratio of (1:1), whereas minimum turbidity result (0.7466 ± 0.0251 NTU) was found in SNEDDS-4 formulation corresponding to (4:1) ratio. Results showed that all the SNEDDS formulations showed minimum turbidity values (less than 100 NTU) in comparison to water (0.6033 ± 0.0568 NTU) as a result of their small particle size, which indicates good miscibility and self-emulsification of theses formulae when introduced into the aqueous acidic medium Czajkowska-Kośnik et al 2015;Kassem et al 2010). All prepared liquid formulations maintained their clarity after 24 h and 48 h storage as illustrated in (Fig.…”
Section: Turbidity Measurementmentioning
confidence: 99%
“…Robustness to dilution refers to a simple evaluation test that consists of diluting SEDDSs 100-fold where, after, dilutions are left at an ambient temperature of approximately 25 • C for a period of 24 h prior to visual inspection to determine if phase separation has occurred [122]. The ability of a SEDDS to withstand drug precipitation as well as phase separation upon exposure to dilution indicates the stability of these simplified systems once introduced to gastrointestinal fluids [6].…”
Section: Robustness To Dilutionmentioning
confidence: 99%